Answer:
b = -6
Step-by-step explanation:
Apply the exponent rule that
In this case, ![\frac{1}{y^{24}} = y^{-24}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7By%5E%7B24%7D%7D%20%20%3D%20y%5E%7B-24%7D)
Set that equal to
:
![(y^{b})^{4} = y^{-24}](https://tex.z-dn.net/?f=%28y%5E%7Bb%7D%29%5E%7B4%7D%20%3D%20y%5E%7B-24%7D)
Apply the exponent rule that
so now you get:
![y^{4b} = y^{-24}](https://tex.z-dn.net/?f=y%5E%7B4b%7D%20%3D%20y%5E%7B-24%7D)
Since the base is y for both sides of the equation, just set the exponents equal to each other and solve for b.
4b = -24
divide each side by 4 to get:
b = -6
Answer:
x=32 degrees
Step-by-step explanation:
We know 180 degrees in triangle
That box means 90 degrees so...
58+90=148
180-148=32
x=32 degrees
Step-by-step explanation:
a/b=662
a%chess issues
8=a/b equals exponent